Development of solid polymer electrolytes based on poly (ethylene oxide) complexed with 2-trifluoromethyl-4, 5-dicyanoimidazole lithium salt and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ionic liquid for Li-ion batteries - Polu, Anji Reddy; Singh, Pramod K.; Kumar, P Siva; Joshi, Girish M; Ramesh, T.; Noor, I. M.; Madkhli, Aysh Y; Kakroo, Sunanda (SAGE Publications, 2022)
Ion conducting solid polymer electrolyte films based on polymer poly (ethylene oxide) (PEO) complexed with 2-trifluoromethyl-4, 5-dicyanoimidazole lithium salt and ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide are synthesized using anhydrous acetonitrile as solvent. Prepared electrolyte films are characterized by X-ray diffraction (XRD), differential scanning calorimetry (DSC), complex impedance spectroscopy and cyclic voltammetry techniques. Incorporation of IL into the PEO20-LiTDI polymer electrolyte changes different physicochemical properties of these materials. By characterizations, particularly XRD, DSC and ionic conductivity studies, the synthesized SPEs showed decreased crystallinity, melting points and increased ionic conductivity by the introduction of ionic liquid. The 40 wt% of IL doped polymer electrolyte showed an ionic conductivity of the order of 1.78 × 10−4 S/cm at 60°C with better thermal stability. The optimum conducting composition showed very good electrochemical stability window at ambient temperature. These results suggested that the IL-doped polymer electrolyte would be a potential separator in Li-ion batteries.